RESTORATION OF THE NATIONAL CULTURE AND HISTORICAL HERITAGE OF UZBEKISTAN (American Journal of Research in Humanities and Social Sciences, 2024)
After the independence of Uzbekistan, several reforms were carried out to restore our national spiritual and cultural heritage in our country. This article focuses on the analysis of the issues on the development of the spiritual and cultural sphere carried out in Uzbekistan during the years of independence and research on the intensification of cooperation relations with UNESCO.